Seroprevalence and real-time PCR study of Epstein-Barr virus and the value of screening in pretransplant patients - Mervat Elansary; Hemmat E El Haddad; Usama A.A. Sharaf Eldin; Ahmed Hamdy; Mai M Sherif (SpringerOpen, 2016)
Objective This study was performed to estimate the prevalence of Epstein-Barr virus immunoglobulin M virus capsid antigen (EBV IgM VCA) among healthy blood donors and to confirm the real risk of transfusion transmission by detection of virus load using PCR quantification. Materials and methods A total of 860 apparently healthy Egyptian blood donors were enrolled and tested for EBV IgM VCA. Quantitative PCR was performed for reactive cases for EBV IgM VCA. Results An overall 38 patients were reactive for EBV IgM VCA, constituting 4.4% of the sample. Reactivity of Epstein-Barr virus did not differ significantly as regards sex distribution, blood grouping, Rh factor positivity, and hemoglobin level, but it was significantly higher among upper Egypt participants than among those from other regions (P = 0.006). There was a very high statistically significant positive correlation between the titer of EBV VCA IgM reactive cases and age in the studied group (P = 0.0001 and r = 0.6). PCR was negative for all of the reactive cases. Conclusion Routine screening for Epstein-Barr virus in blood bags is not economical. Screening is highly recommended only for immunocompromised and pretransplant patients. Viremia is not the role in individuals with EBV IgM positive sera, which in turn changes some concepts in organ transplantation.